Determinants of the Employee's Performance - Nisa, Dzurotun; Nurhidayati, Anik (Journal of Applied Management Research, 2024)
Government institutions such as the Office of the Ministry of Religion must be able to serve the community, especially in the field of religion. The success of this government institution cannot be separated from the role of its employees, namely employee performance. This research was conducted to demonstrate the effects of motivation, work stress and organisational culture on performance of workers at Rembang Regency's Office of the Ministry of Religious Affairs. In this study, 55 employees of the Rembang Religious Office were involved. Sample: This study used a saturated sample, totalling 55 respondents. To analyze the data, multiple linear regression analysis was employed. The study has findings: the motivation variable has an insignificant influence on employee performance; the work stress variable has an insignificant influence on employee performance; and the organisational culture variable has a significant influence on employee performance. The determination of variability in the dependent variable, employee performance, can be partially explained by the independent variables, namely motivation, job stress, and organisational culture. Additional independent variables that are not explained in this study, account for 53.8%. These results suggest that the performance of the employees is quite good, but needs to be improved. This finding is expected to be a consideration for related parties in organising internal management so that it can attain the goals that are set.